2002
DOI: 10.1007/s004410100466
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neuroactive substances on the activity of subcommissural organ cells in dispersed cell and explant cultures

Abstract: The subcommissural organ (SCO), an ependymal (glial) circumventricular organ, releases glycoproteins into the cerebrospinal fluid; however, the regulation of its secretory activity is largely unknown. To identify neuroactive substances that may regulate SCO activity, we investigated immunocytochemically identified bovine SCO cells by means of calcium imaging. This analysis was focused on: (1) serotonin (5HT) and substance P (SP), immunocytochemically shown to be present in axons innervating the bovine SCO; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…The presence of low-affinity glucose transporters, such as GLUT2, would allow continuous glucose uptake, which could eventually lead to rapid increases in ATP concentration, as has been previously described in tanycytes and β-pancreatic cells [2,4,25]. Additionally supporting this hypothesis, previously it was found that an increase in intracellular ATP content in SCO cells elicited rises in [Ca 2+] i in 85% of analyzed cells [24]. These effects were dose dependent and involved NK 3 and P 2 Y 2 receptors linked to G protein and PLC activation.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…The presence of low-affinity glucose transporters, such as GLUT2, would allow continuous glucose uptake, which could eventually lead to rapid increases in ATP concentration, as has been previously described in tanycytes and β-pancreatic cells [2,4,25]. Additionally supporting this hypothesis, previously it was found that an increase in intracellular ATP content in SCO cells elicited rises in [Ca 2+] i in 85% of analyzed cells [24]. These effects were dose dependent and involved NK 3 and P 2 Y 2 receptors linked to G protein and PLC activation.…”
Section: Discussionsupporting
confidence: 68%
“…These effects were dose dependent and involved NK 3 and P 2 Y 2 receptors linked to G protein and PLC activation. In all ATP-sensitive cells, the increase in the [Ca 2+ ]i involves calcium release from thapsigargin-sensitive intracellular stores and PKC-mediated influx of extracellular calcium via L-type voltage-gated calcium channels (VGCCs) [ 24 ]. Thus, SCO cells would have the capacity to respond to increased glucose concentrations, increasing their apical secretion and SCO-spondin solubilization in CSF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The copyright holder for this preprint this version posted April 12, 2024. ; https://doi.org/10.1101/2024.04.09.24305433 doi: medRxiv preprint in CSF 15,19,20 . It receives neural input, and is under neural control from multiple neural transmitter systems such as GABA, dopamine, noradrenaline and serotonin [21][22][23] , suggesting that it may be involved in stress response and mood regulation, because these neurotransmitters control basic emotions and are implicated in affective disorders 24 . Like other circumventricular organs (CVO), the SCO has axon terminals from the hypothalamus, secreting neurohormones, supporting that the SCO is functionally linked to the hypothalamus 25 .…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%